2022
DOI: 10.2147/pgpm.s354011
|View full text |Cite
|
Sign up to set email alerts
|

Is Pharmacogenetic Panel Testing Applicable to Low-Dose Methotrexate in Rheumatoid Arthritis? – A Case Report

Abstract: Purpose Pharmacogenetic (PGx) panel testing could help to determine the heritable component of a rheumatoid arthritis (RA) patient’s susceptibility for therapy failure and/or adverse drug reactions (ADRs) from methotrexate (MTX). Considering the literature mentioning the potential applicability of PGx panel testing within MTX regimens, we discuss the case of a patient who was treated with MTX, suffered from ADRs, and obtained a reactive PGx panel testing. Genotyping We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 44 publications
(80 reference statements)
0
3
0
Order By: Relevance
“…Previous studies have revealed the influence of various SNPs on the toxicity of MTX in patients with autoimmune diseases, such as MTHFR, MTR, ABCC1, ABCC2, and ABCG2 [ 72 , 73 , 74 ]. However, the existing evidence on the influence of genetics on MTX toxicity in patients with PS is limited.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have revealed the influence of various SNPs on the toxicity of MTX in patients with autoimmune diseases, such as MTHFR, MTR, ABCC1, ABCC2, and ABCG2 [ 72 , 73 , 74 ]. However, the existing evidence on the influence of genetics on MTX toxicity in patients with PS is limited.…”
Section: Discussionmentioning
confidence: 99%
“…Following the referral by the treating physician, the recruited patients underwent the process, as depicted in Figure 1 . Individual cases from the series were published as case reports [ 21 , 22 , 23 , 24 , 25 , 26 ]. The work experience that was gathered within the observational case series study was used to further refine the PGx service over the duration of 3 years between 2019 and 2021, and was based on feedback from patients and treating physicians that was further elaborated in a mixed methods study [ 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…7 This study was designed to compile case reports to acquire experience with the application of PGx in Swiss primary and secondary care as a basis for the implementation of a standard of procedure. After three years of collecting those patient cases and publishing selected individual case reports, [14][15][16][17][18][19] we aimed to perform a database analysis of all gathered data of the study population.…”
Section: Introductionmentioning
confidence: 99%